URGENSI MEMAHAMI PERKEMBANGAN BAHASA ANAK - Rumbaroa, Reza Hasbullah (LP2M IAIN Ambon, 2020)
Abstract Babies in a few months will develop speech starting from crying, screaming, pronouncing one word to one sentence or even one paragraph. If you look at the current reality, it shows that the child's ability to acquire language is still weak. For this reason, researchers aim to provide understanding or solutions related to the development of children's language mastery. The method in this research is a qualitative approach with library research. Sources of data reviewed in this study come from primary data and secondary data. Collecting data from text books and journals. Parents should fully understand the stages of children's language development and know their role in stimulating children's language development. The results of this study indicate that the development of children's language includes several stages. Pre-linguistic stage starting from 0-1 years is characterized by crying, screaming, laughing, and imitating movements. Furthermore, the linguistic stage from the age of 1-5 years is marked by the pronunciation of one vowel letter to 2 words and begins to understand the meaning of the word at the age of 1-2 years. 3-4 years old children understand pronouns, verbs, question words, surrounding nouns and read some letters and mastery of words around 65%. Age 5-6 years old children understand the meaning of words, say colors, count numbers, understand the meaning of sentences, read and write all letters and word mastery around 85%. Can communicate well understand 1500-2500 words. Of course, this development is influenced by several factors, namely health factors, intellectual intelligence, economy, gender and family relations. Key Words: urgency, understanding, language development, Abstrak Bayi dalam beberapa bulan akan mengalami perkembangan berbicara mulai dari menangis, berteriak, pengucapan satu kata hingga satu kalimat bahkan satu paragraf. Jika melihat realita saat ini menunjukan kemampuan anak dalam memperoleh bahasa masih lemah. Untuk itulah, peneliti bertujuan untuk memberikan pemahaman atau solusi terkait perkembangan penguasaan bahasa anak. Metode dalam penelitian ini adalah pendekatan kualitatif dengan penelitian pustaka. Sumber data yang ditinjau dalam penelitian ini berasal dari data primer dan data sekunder. Pengumpulan data dari buku teks dan jurnal. Orang tua seharusnya memahami tahap-tahap berkembangan bahasa anak sepenuhnya dan mengetahui perannya dalam memberi stimulus perkembangan bahasa anak. Hasil Penelitian ini menunjukan bahwa perkembangan bahasa anak meliputi beberapa tahap. Tahap Pra Linguistik dimulai dari 0-1 tahun ditandai dengan menangis, menjerit, tertawa, hingga menirukan gerakan. Selanjutnya pada tahap Linguistik daru usia 1-5 tahun ditandai dengan pengucapan satu vokal huruf hingga 2 kata dan mulai memahami makna kata pada usia 1-2 tahun. Usia 3-4 tahun anak memahami kata ganti, kata kerja, kata tanya, kata benda sekitar serta membaca beberapa huruf dan penguasaan kata sekitar 65%. Usia 5-6 tahun anak memahami makna kata, menyebutkan warna, menghitung angka, memahami maksud kalimat, baca tulis semua huruf dan penguasaan kata sekitar 85%. Dapat berkomunikasi dengan baik memahami 1500-2500 kata. Tentunya perkembangan ini dipengaruhi oleh beberapa faktor yakni faktor kesehatan, kecerdasan intelektual, ekonomi, gender dan hubungan keluarga. Kata Kunci: urgensi, pemahaman, perkembangan bahasa.